Comparison of right ventricular septal pacing and right ventricular apical pacing in patients receiving cardiac resynchronization therapy defibrillators: the SEPTAL CRT Study - Leclercq, Christophe (Eur Heart J, 2016)
AIMS: Cardiac resynchronization therapy (CRT) is a recommended treatment of heart failure (HF) patients with depressed left ventricular ejection fraction and wide QRS. The optimal right ventricular (RV) lead position being a matter of debate, we sought to examine whether RV septal (RVS) pacing was not inferior to RV apical (RVA) pacing on left ventricular reverse remodelling in patients receiving a CRT-defibrillator. METHODS AND RESULTS: Patients (n = 263, age = 63.4 ± 9.5 years) were randomly assigned in a 1:1 ratio to RVS (n = 131) vs. RVA (n = 132) pacing. Left ventricular end-systolic volume (LVESV) reduction between baseline and 6 months was not different between the two groups (−25.3 ± 39.4 mL in RVS group vs. −29.3 ± 44.5 mL in RVA group, P = 0.79). Right ventricular septal pacing was not non-inferior (primary endpoint) to RVA pacing with regard to LVESV reduction (average difference = −4.06 mL; P = 0.006 with a −20 mL non-inferiority margin). The percentage of ‘echo-responders’ defined by LVESV reduction >15% between baseline and 6 months was similar in both groups (50%) with no difference in the time to first HF hospitalization or death (P = 0.532). Procedural or device-related serious adverse events occurred in 68 patients (RVS = 37) with no difference between the two groups (P = 0.401). CONCLUSION: This study demonstrates that septal RV pacing in CRT is non-inferior to apical RV pacing for LV reverse remodelling at 6 months with no difference in the clinical outcome. No recommendation for optimal RV lead position can hence be drawn from this study. CLINICALTRIALS. GOV NUMBER: NCT 00833352.